Mixed-Integer Linear Programming Model for the Super-Colored Path Problem in Digraphs - Marian, Rafael; Ataide, Wesly Carmesini; Santiago, Rafael de; Franco, Álvaro Junio Pereira (Anais do Encontro de Teoria da Computação (ETC), 2026)
This paper presents a method based on Mixed-Integer Linear Programming (MILP) to solve the Super-Colored Path Problem. Given a digraph D with colored vertices, and for each vertex v in D, we want to find the maximum number of distinct colors that a simple path starting from v can take. The proposed method draws resemblance with the classic formulation for solving the Traveling Salesman Problem, in particular the presence of subtours.